ANALISIS TINGKAT PELAYANAN RESTORAN TERHADAP KEPUASAN PELANGGAN: STUDI KASUS PADA DUA RESTORAN DI KOMPLEKS PERTOKOAN WAY HALIM PERMAI KOTA BANDAR LAMPUNG - Aryanti, Dwi; Hudoyo, Agus; Kasymir, Eka (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2013)
Population and economic growth in Bandar Lampung has been increasing the demand of restaurants. Consequently, competition among restaurants in Bandar Lampung has been increasing in order to get their customers. The main goal of this research is to find out the difference between the customers’ expectation and the restaurant’s performance. Data were obtained form questioning respondents from two restaurants in the business area of Way Halim Permai, Bandar Lampung. Data were analyzed using the Importance Performance Analysis (IPA). It is revealed that both Restaurant A and Restaurant B were under performed in two atributes, i.e. restaurant comfort and hospitality. Spesifically, Restaurant A was under performed in the taste of its food and Restaurant B was under performed in cleanness and tidiness; restroom availability; and wastafel/washing stand availability. Keywords: atributes, importance, performance, Importance Performance Analysis (IPA), restaurant’s